2020
DOI: 10.3389/fnhum.2020.00169
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal Neural Synchronization During Cooperative Behavior of Basketball Players: A fNIRS-Based Hyperscanning Study

Abstract: Accumulating evidence has consistently shown that team-based sports (such as basketball) are beneficial to interpersonal cooperation. However, its neural correlate remains to be discovered, especially in the perspective of two-person neuroscience. In this study, 12 dyads of basketball players and 12 dyads of college students who had no experience of team-based sports training were asked to perform joint-drawing task and control task. During task performance, neural activities were recorded in frontal area by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 46 publications
(50 reference statements)
2
17
0
Order By: Relevance
“…Specifically, some studies that have used fNIRS for social processes investigation have observed a greater activation of prefrontal areas, such as the dorsolateral prefrontal cortex (DLPFC), most involved in the implementation of co-operative behaviors (Balconi et al, 2019a, 2019b, 2020; Balconi & Pagani, 2014, 2015) and in the management of social interactions (Balconi & Molteni, 2016; Kalbe et al, 2010). In particular, as reported by previous studies, during the performance of co-operative tasks, unlike those of control, an increase of the interpersonal neural synchronization (INS) occurs in the prefrontal area (Li et al, 2020; Lindenberger et al, 2009; Metzger et al, 2017).…”
supporting
confidence: 59%
“…Specifically, some studies that have used fNIRS for social processes investigation have observed a greater activation of prefrontal areas, such as the dorsolateral prefrontal cortex (DLPFC), most involved in the implementation of co-operative behaviors (Balconi et al, 2019a, 2019b, 2020; Balconi & Pagani, 2014, 2015) and in the management of social interactions (Balconi & Molteni, 2016; Kalbe et al, 2010). In particular, as reported by previous studies, during the performance of co-operative tasks, unlike those of control, an increase of the interpersonal neural synchronization (INS) occurs in the prefrontal area (Li et al, 2020; Lindenberger et al, 2009; Metzger et al, 2017).…”
supporting
confidence: 59%
“…Over time, these interpersonal connections may lead to increased engagement which may be correlated with the functional outcomes of each patient such as motor learning or skill acquisition. A previous study in healthy individuals supports this hypothesis, showing that there is greater behavioral synchrony and inter-brain synchronization between basketball teammates compared to strangers during a joint drawing task [ 58 ]. Additionally, the influence of Patient–Machine interactions could be explored in larger groups as well.…”
Section: Future Considerations: Hyperscanning In Patient Populationsmentioning
confidence: 70%
“…In one of them, participants tried to synchronize their taps (cooperation) or be faster than the co-actor (competition; Cui et al, 2012 ), while in the other study, bidirectional and unidirectional tapping was compared ( Dai et al, 2018 ). Lastly, one study compared interbrain synchrony in joint (synchronized) versus independent drawing ( Li et al, 2020 ). In sum, various types of tasks were found to study cooperation and interbrain synchrony with fNIRS.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, different subparts of PFC were reported to be synchronized in different tasks. One set of studies (six studies, Xue et al, 2018 ; Lu and Hao, 2019 ; Lu et al, 2019a , b ; Y. Li et al, 2020 ; Sun et al, 2020 ) that required flexibility in solving a problem (realistic, creativity, and math problems) or drawing together show interbrain synchrony in dorsolateral PFC (DLPFC). One of the primary functions of DLPFC reported in intra brain studies is cognitive flexibility related to attention switch ( Monsell, 2003 ).…”
Section: Resultsmentioning
confidence: 99%